An Anesthetist’s Experience and the Incidence of Critical Cases in Ambulatory Surgery - R. V. Bolshedvorov; V. V. Likhvantsev (Общая реаниматология, 2009)
Objective: to evaluate the impact of experience on the quality of anesthesia in ambulatory surgery. Materials and methods. The authors undertook a study of the role of experience and specialization on the occurrence of complications in ambulatory anesthesia care. By using the internal audit and calculating the frequency of critical cases, they examined the results of the work of two groups of anesthetists: 1) medical beginners after 2-year adjunct practice and 2) one-day hospital specialists having an at least 7-year practice length. Results. In the beginner group, the number of critical cases per operation was twice higher than that in the experienced specialists. The paper shows the detrimental pattern of the residual principle in selecting anesthetists for work at a one-day hospital and provides evidence that specialization is required in the area under discussion. Key words: ambulatory anesthesiology, role of an anesthetist’s experience, critical cases.